PENGARUH PEMBERIAN KOMBINASI AMPAS TAHU DAN LIMBAH ROTI AFKIR YANG DIFERMENTASI SEBAGAI NUTRISI TERHADAP PERTUMBUHAN DAN PRODUKSI MAGGOT (Hermetia illucens) - Febry Ferdiyanto Purba; T. Iskandar Johan; Muhammad Hasby (DINAMIKA PERTANIAN, 2022)
This study aims to determine the effect of giving a combination of tofu pulp and fermented bread on the growth and production of maggots. The method used is a complete Randomized Design (RAL) 5 treatments with 3 tests, namely, P1: Tofu dregs (100%), P2: tofu dregs (75%) + afkir bread (25%), P3: tofu dregs (50%) + afkir bread (50%), P4: tofu dregs (25%) + afkir bread (75%) and P5: afkir bread (100%). The results of the study obtained the best combination of nutrients, namely P3with a weight growth of 0.236 gr and a length growth of 2.00 cm. From the results of the protein content test, the highest maggot protein at P5 was obtained at 43.09%. While the measurement of maggot media obtained a temperature of 34-40oC and a pH of 4.5-7.